Region-specific differences in bioenergetic proteins and protein response to acute high fat diet in brains of low and high capacity runner rats. (1st May 2018) - Gan, Li; Ma, Delin; Li, Min; Yang, Fu-Chen; Rogers, Robert S.; Wheatley, Joshua L.; Koch, Lauren G.; Britton, Steven L.; Thyfault, John P.; Geiger, Paige C.; Stanford, John A.
Highlights: PGC1-α, Nrf-1, and TFAM were lower in the striatum of LCR rats. p-AMPK was greater in the striatum of LCR rats. Striatal PGC1-α, Nrf-1, TFAM, and pAMPK were responsive to an acute HFD in LCR rats. Markers did not differ in substantia nigra, hippocampus, or hypothalamus. Abstract: Aerobic capacity is a strong predictor of mortality. Low capacity runner (LCR) rats exhibit reduced mitochondrial function in peripheral organs. A high fat diet (HFD) can worsen metabolic phenotype in LCR rats. Little is known about metabolic changes in the brains of these rats, however. This study examined protein markers of mitochondrial function and metabolism as a function of aerobic running capacity and an acute HFD in four brain regions: the striatum, hippocampus, hypothalamus, and substantia nigra. After 3 days HFD or chow diets, we measured peroxisome proliferator-activated receptor-γ coactivator 1α (PGC1-α), nuclear respiratory factors 1 (Nrf-1), mitochondrial transcription factor A (TFAM), and phosphorylated (activated) AMP-activated protein kinase (p-AMPK) protein levels in the four brain regions. LCR rats exhibited lower levels of mitochondrial proteins (PGC1-α, Nrf-1, TFAM), and greater p-AMPK, in striatum, but not in the other brain regions. Mitochondrial protein levels were greater in HFD LCR striatum, while p-AMPK was lower in this group. Markers of lower mitochondrial biogenesis and increased metabolic demand were limited to the LCR striatum, which nevertheless maintained the capacity to respond to an acute HFD challenge.